THE ROLE OF CULTURAL AWARENESS IN ENHANCING COMMUNICATIVE COMPETENCE IN EFL CLASSROOMS - Turgunova Shokhsanam Alisherovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Cultural awareness has become a cornerstone of successful communication in English as a Foreign Language (EFL) contexts. As English grows into a global lingua franca, mere grammatical competence is no longer sufficient; students must also be able to interpret, navigate, and respond appropriately to diverse cultural norms. This paper explores how integrating cultural elements into EFL instruction enhances learners’ communicative competence. Drawing on established theories and classroom examples, the study argues that awareness of cultural nuances enables learners to better manage real-life interactions and avoid miscommunication.